Some Critiques that Can Be Made from Levinas to the Notion of "Justice" of Paul Ricœur and John Rawls - Medina Delgadillo, Jorge (2015)
The  well  known  conference  of  Paul  Ricœur ‘Love and Justice’, pronounced when he received Leopold Lucas award in 1989, shows a dialectical tension between those two notions, and searches deeper in the philosophical –and even theological– basis that reveals love as rectification and safeguard of justice; without love, justice would be cruel, utilitarian and, paradoxically, unfair, remembering us the old Roman adage: “summum ius, summa iniuria”. Moreover, Levinas, in his “Talmudic Lesson on Justice”, compiled after in New Talmudic Readings, presents a less intuitive position, but no less interesting: justice is the place of forgiveness and love, it becomes humane everything it touches, and that’s why it doesn’t need correction; a justice that needed love, had maybe never been true justice. Here lies a critic that complements and improves both, the theory exposed by Paul Ricœur and its Rawlsian basis.